Conditions for high-potential female entrepreneurship - Siri A. Terjesen (IZA World of Labor, 2016)
Female-led ventures that are market-expanding, export-oriented, and innovative contribute substantially to local and national economic development, as well as to the female entrepreneur's economic welfare. Female-led ventures also serve as models that can encourage other high-potential female entrepreneurs. The supply of high-potential entrepreneurial ventures is driven by individuals' entrepreneurial attitudes and institutional factors associated with a country's conditions for entrepreneurial expansion. A systematic assessment of those factors can show policymakers the strengths and weaknesses of the environment for high-potential female entrepreneurship.
Keywords: L26; J16; N30; C43; B54; 330; female entrepreneurship; high-potential entrepreneurship; institutions; export-oriented ventures; high-growth start-up